Labour and the Politics of Disloyalty in Belfast, 1921-39 The Moral Economy of Loyalty - Loughlin, Christopher J. V. (Springer International Publishing, 2018)
This book provides the first 'history from below' of the inter-war Belfast labour movement. It is a social history of the politics of Belfast labour and applies methodology from history, sociology and political science. Christopher J. V. Loughlin questions previous narratives that asserted the centrality of religion and sectarian conflict in the establishment of Northern Ireland. Labour and the Politics of Disloyalty in Belfast, 1921-39 suggests that political division and violence were key to the foundation and maintenance of the democratic ancien régime in Northern Ireland. It examines the relationship between Belfast Labour, sectarianism, electoral politics, security and industrial relations policy, and women's politics in the city. .